Formulation and Characteristics of Sunscreen Cream based on Isolated Lignin from Oil Palm Empty Fruit Bunch (OPEFB) : Formulation and Characteristics of Sunscreen Cream - Restu, Witta Kartika; Rusumayanti, Felli; Septiyanti, Melati; Muryanto; Aryana, Nurhani; Mawarni, Rista Siti; Meliana, Yenny; Sondari, Dewi; Fatriasari, Widya; Ogino, Chiaki (BRIN Publishing (Penerbit BRIN), 2025)
Lignin was recovered from black liquor during the biorefinery process and has prospective applications in pharmaceutical, cosmetic, and health care. Lignin, which has substantially smaller particles, was used as the active ingredient in the sunscreen cream formulation. The isolated lignin was examined for physicochemical parameters such as yield, purity, particle size, total phenol, and morphology. The obtained lignin was used in the preparation of sunscreen cream. The isolated lignin concentration in the cream varied between 0.1, 1, and 2 wt%. The sun protection factor (SPF) of the designed sunscreen creams was assessed, and antioxidant activity and stability were studied, which included pH, particle size, and appearance during the observation period. The formulated cream has an SPF of approximately 15, which is sufficient to protect human skin from the sun's UV radiation. Furthermore, the most significant antioxidant activity was found to be 68.94%. As a result, the developed sunscreen cream has the potential for further research because it is composed of natural active ingredients that are safe for humans and the environment.